Thermal and kinetic performance analysis of corncobs, Falsa sticks, and Chamalang coal under oxidizing and inert atmospheres. Issue 8 (18th April 2017) - Munir, Shahid; Sattar, Hamed; Nadeem, Ali; Azam, Mudassar
ABSTRACT: This article investigates the thermal and kinetic behaviors of Pakistani corncob (Cc) and Falsa sticks (FS) under inert (N2 ) and oxidative (dry air) atmospheres using a nonisothermal thermogravimetric method. Maximum rates of weight loss, peak temperature, combustion factor, pyrolysis factor, mean reactivity, order of reaction, and activation energies were evaluated and correlated. Mean reactivities were found to be Cc = 0.52 > FS = 0.51 > Chamalang coal = 0.05 for pyrolysis and Cc = 0.75 > FS = 0.67 > Chamalang coal = 0.08 for oxidative environment. The pyrolysis factor and combustion characterization factor were found to be higher for biomass fuels compared to coal.